2017
DOI: 10.1371/journal.pone.0178401
|View full text |Cite
|
Sign up to set email alerts
|

Does published research on non-communicable disease (NCD) in Arab countries reflect NCD disease burden?

Abstract: ObjectivesTo review trends in non-communicable (NCD) research output in the Arab region, in terms of quantity and quality, study design, setting and focus. We also examined differences by time and place, and assessed gaps between research output and NCD burden.MethodsA scoping review of a total of 3,776 NCD-related reports published between 2000 and 2013 was conducted for seven Arab countries. Countries were selected to represent diverse socio-economic development levels in the region: Regression analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
(26 reference statements)
2
22
0
Order By: Relevance
“…The status of the health-research system in the Arab world has been described previously in numerous areas of health such as dengue research [21], pharmaceutical wastewater research [57], integrative and complementary medicine research [58], toxicology research [59], tobacco smoking research [60], breast cancer research [61], and infectious disease research [62]. Health-research systems in the Arab world are perceived as being non-productive system due to low priority in national research funding levels and development planning [63][64][65]. Despite the health services have improved in some Arab countries especially those with oil-based economies, the performance and development of their health-research system are lower than expected [66].…”
Section: Discussionmentioning
confidence: 99%
“…The status of the health-research system in the Arab world has been described previously in numerous areas of health such as dengue research [21], pharmaceutical wastewater research [57], integrative and complementary medicine research [58], toxicology research [59], tobacco smoking research [60], breast cancer research [61], and infectious disease research [62]. Health-research systems in the Arab world are perceived as being non-productive system due to low priority in national research funding levels and development planning [63][64][65]. Despite the health services have improved in some Arab countries especially those with oil-based economies, the performance and development of their health-research system are lower than expected [66].…”
Section: Discussionmentioning
confidence: 99%
“…A study on health research outputs in Palestine indicates the presence of a mismatch between the health burden of certain disease conditions and the number of published research reports on those diseases (82). Such discordance between research output and disease burden was also demonstrated in a study that covered research on noncommunicable diseases in seven Arab countries (68). These pioneering observations are enough reason to further explore the qualitative, organizational, and social characteristics of biomedical and health research in the EMR and how it is aligned with the major health priorities in the Region.…”
Section: Géographie De La Recherche En Biomédecine Et En Santé Dans Lmentioning
confidence: 94%
“…While the increase of biomedical and health research productivity in Egypt, Islamic Republic of Iran, and Saudi Arabia could be attributed to the considerable support for scientific and health research in these countries (68), the stagnant development of biomedical and health research in other parts of the EMR is attributed to the weak support to national health research systems in the Region (7), as well as to major socio-political instabilities that downplayed scientific endeavours in some of the most research-active countries.…”
Section: The Fragility Of Biomedical and Health Research In The Emrmentioning
confidence: 99%
“…There is a growing epidemiological literature on NCDs in the Middle East, North Africa, and Turkey [5,29,30] which highlights regional characteristics of this global problem, as well as the related challenge for national health systems [31,32]. Some of this evidence stems from our own research in MedCHAMPS: in particular from comparative country-level analyses of epidemiological data, which depict more heterogeneous trends [6,27] than is apparent from recent Global Burden of Disease (GBD) studies of cardiovascular risk factor trends across the Middle East and North Africa (MENA) region [33].…”
Section: Context and Challengesmentioning
confidence: 99%